Analysis of the Influence of Celebrity Endorsers: Case Study of Audience Attitudes towards Advertising and Brands and the Influence of Consumer Purchase Interest on the Product "Lemonilo X NCT Dream" in Bekasi - Putri, Amanda Dwi; Hadita, Hadita (Formosa Journal of Applied Sciences, 2024)
Given the importance of the needs that must be met by humans as living beings, food is one of the elements that must be fulfilled so that humans can survive. Food is increasingly innovating but until now instant food is still favored by many people. Instant food that is often found and easy to make is Instant Noodles, there are many Instant Noodle brands in Indonesia, especially Lemonilo. Lemonilo does its marketing strategy by hooking NCT Dream as its celebrity endorser or brand ambassador. It is said to be the right decision because it turns out that celebrity endorsers through audience attitudes towards advertising and brands have a significant positive influence on buying interest in Lemonilo products.